2016
DOI: 10.3389/fpsyg.2016.00492
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Subjective Experience and EEG Biomarkers Are Associated with Sleep-Onset Latency

Abstract: Difficulties initiating sleep are common in several disorders, including insomnia and attention deficit hyperactivity disorder. These disorders are prevalent, bearing significant societal and financial costs which require the consideration of new treatment strategies and a better understanding of the physiological and cognitive processes surrounding the time of preparing for sleep or falling asleep. Here, we search for neuro-cognitive associations in the resting state and examine their relevance for predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 71 publications
1
22
1
Order By: Relevance
“…The question arises as to whether fractal dimension and Hurst exponent provide additional information to spectral features in describing the rest conditions. Previous studies reported evidence that variation in spectral and fractal feature of EEG can be linked to retroactive self-reports of subjective experiences at rest (Knyazev, 2013 ; Diaz et al, 2016 ). Even if with an exploratory purpose, we separately performed a regression analysis for each factor of ARSQ, considered as dependent variable, and with fractal dimension, scaling exponents and band powers as independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…The question arises as to whether fractal dimension and Hurst exponent provide additional information to spectral features in describing the rest conditions. Previous studies reported evidence that variation in spectral and fractal feature of EEG can be linked to retroactive self-reports of subjective experiences at rest (Knyazev, 2013 ; Diaz et al, 2016 ). Even if with an exploratory purpose, we separately performed a regression analysis for each factor of ARSQ, considered as dependent variable, and with fractal dimension, scaling exponents and band powers as independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relationship of commonly observed resting-state microstates to psychological domains of resting is not clear. Recently, the Amsterdam Resting-State Questionnaire (ARSQ) was introduced (Diaz et al 2013;Diaz et al 2014), offering an effective way to quantify subjective states after a period of resting in a number of domains (Theory of Mind, Discontinuity of Mind, Self, Planning, Somatic Awareness, Sleepiness, Comfort, Health Concern, Visual Thought, Verbal Thought ) and associate these quantifiers to psychological and physiological variables (Diaz et al 2013;Stoffers et al 2015;Diaz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marchetti et al [ 26 ] demonstrated that individuals with high values on the dimension “Theory of Mind” showed higher functional connectivity in the frontal lobe and in the insula, with a dominance of the left hemisphere, suggesting that connectivity within the frontal lobes facilitates mentalizing ability. Others [ 27 , 28 ] identified associations of several dimensions of the ARSQ with alpha and theta oscillations during rest and with sleep latency. These results suggest that the ARSQ assesses dimensions of ST as rather stable, trait-like characteristics and provide first indications for construct validity with respect to neural correlates of ST as assessed by this questionnaire in nonclinical populations.…”
Section: Introductionmentioning
confidence: 99%